Bioactive composition and anti-hyperglycemic properties of biofortified yellow maize-based gluten-free cookies - Abdulrazaaq, Khadijat Oluwashola; Imam, Yunus Temitayo; Irondi, Emmanuel Anyachukwu; Ajani, Emmanuel Oladipo (Frontiers in Food Science and Technology, 2024)
The use of gluten-free ingredients in the baking of cookies is increasing due to gluten-associated disorder and other nutritional-related non-communicable diseases, and consumer's pursuit for health-promoting foods. In this study, gluten-free cookies (GFC) were made from biofortified yellow maize supplemented with sodium carboxyl methylcellulose (SCMC), a reference hydrocolloid, and Brachystegia eurycoma flour (BEF) at four different proportions (2.5, 5, 7.5, and 10%), respectively. The GFC were then assessed for their bioactive components (flavonoids, tannins, and saponins), carotenoids, starch-hydrolyzing enzymes (alpha-amylase and alphaglucosidase), and glycemic index. Cookies made from commercial wheat flour (100% CWF) served as control. The total flavonoid contents of the 100% BYF cookies (144.48 ± 0.18 mg/g) and saponins (1.04 ± 0.00 mg/g) were significantly (p < 0.05) higher than the 100% CWF cookies (93.84 ± 0.36 mg/g; 1.02 ± 0.00 mg/g). The total tannin contents of the cookies ranged from 3.12 ± 0.00 mg/g (100% CWF) to 4.87 ± 0.00 mg/g (2.5%BEF-97.5% BYF). The carotenoid profiles indicated the presence of lutein (range from 0.62 to 1.63 μg/g), β-carotene (range from 3.81 to 6.06 μg/g), β-cryptoxanthin (range from 0.19 to 1.75 μg/g) and zeaxanthin (range from 0.83 to 2.48 μg/g) in the cookies. Further, the GF cookies significantly (p < 0.05) inhibited the alpha-amylase (IC50 value ranged from 1.42 ± 0.01 μg/mL (100% BYF) to 2.63 ± 0.01 μg/mL (100% CWF)) and alpha-glucosidase with IC50 value range from 1.12 ± 0.01 μg/mL (2.5%SCMC-97.5% BYF) to 6.72 ± 0.01 (7.5%BEF-92.5% BYF). The GF cookies showed a low glycemic index (GI) value (GI < 50). The biofortified yellow maize-based GFC have significant amounts of bioactive compounds and anti-hyperglycemic properties, and low GI. Hence, they can serve as functional baked food with potential health benefits.